Acupuncture improved hepatic steatosis in HFD-induced NAFLD rats by regulating intestinal microbiota - Wang, Haiying; Wang, Qiang; Liang, Cuimei; Pan, Liang; Hu, Hui; Fang, Hongjuan (Frontiers in Microbiology, 2023)
Background: Intestinal dysbiosis has been increasingly implicated in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Acupuncture has been shown to have a beneficial effect on NAFLD, but the mechanism is not yet clear. This study explores the potential beneficial effect of acupuncture on intestinal microbiota in NAFLD. Methods: An NAFLD model in Sprague Dawley rats was established with a high fat diet (HFD) for 10 weeks. NAFLD rats were randomly divided into control, model, and acupuncture groups. Following acupuncture treatment over 6 weeks, automated biochemical analysis was used to measure serum lipid metabolism parameters including levels of alanine transferase, aspartate transferase, alkaline phosphatase, total cholesterol, triglycerides, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol. The level of serum inflammatory factors interleukin (IL)-6, IL-10, and tumor necrosis factor-alpha (TNF-α) were measured by enzyme-linked immunosorbent assay. The characteristics of steatosis were evaluated with quantitative computed tomography, hematoxylin and eosin staining, and Oil Red O staining in the liver, while the intestinal microbiota was measured by 16S rRNA gene sequencing. Results: Acupuncture decreased systemic inflammatory response, ameliorated dyslipidemia, and improved liver function indexes in NAFLD model rats. Tomography and staining indicated that acupuncture reduced steatosis and infiltration of inflammatory cells in the liver. 16S rRNA analysis showed that acupuncture reduced the Firmicutes to Bacteroidetes (F/B) ratio, increased the abundance of microbiota, including Bacteroidales_S24-7_group, Prevotellaceae, Bacteroidaceae, Blautia, norank_f_Bacteroidales_S24-7_group, Bacteroides, and Prevotella_9, and decreased the abundance of Ruminococcaceae_UCG-014. Correlation analysis suggested a close correlation between lipid metabolism, inflammation factors, hepatic steatosis, and the changed intestinal microbiota. Conclusions: Acupuncture can significantly improve the lipid metabolism and systemic inflammatory response in HFD-induced NAFLD rats, potentially through regulating the composition of intestinal microbiota.